Fast and High‐Resolution Ultrasound Pressure Field Mapping Using Luminescent Membranes. Issue 12 (31st March 2021) - Michels, Simon E.; Kersemans, Mathias; Versluis, Michel; Lajoinie, Guillaume; Smet, Philippe F.
Abstract: Ultrasound is used extensively in medical imaging and therapy, non‐destructive testing, flow sensing, underwater range assessment, and acoustic microscopy. To ensure the accuracy of these techniques, detailed knowledge of the acoustic pressure field produced by the ultrasonic transducer is required. This paper proposes a functional polymer membrane loaded with ultrasound‐activated luminescent microparticles. The semitransparent membrane makes use of the luminescent properties of BaSi2 O2 N2 :Eu 2+ to convert ultrasonic pressure into visible light in a fast and straightforward way, through a process termed acoustically produced luminescence (APL). APL is shown to work within a wide range of acoustic frequencies (1–25 MHz) and pressures (50 kPa–4.5 MPa), and enables a quantitative characterization of ultrasound fields with a lateral spatial resolution below 200 µm. At the investigated pressures and frequencies, the light generation mechanism is essentially related to ultrasonic heating rather than mechanical stimulation. These membranes offer effective field mapping possibilities, much faster than conventional time consuming point‐by‐point hydrophone scanning. Abstract : Acoustically produced luminescence (APL) employs a specially designed luminescent membrane to convert ultrasound pressure into visible light, producing cross sectional views of the acoustic beam many times faster than conventional hydrophone scanning. This paper demonstrates the ultrasonic heating mechanism behind the light generation, as well as the easy calibration, frequency dependency, and good spatial resolution of the APL method.